2017
DOI: 10.1002/ijgo.12238
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of extended oral contraception use on the prevalence of fetal trisomy 21 in women aged at least 35 years

Abstract: Fewer ovulatory cycles, potentially resulting from longer oral contraceptive pill use, was associated with healthy fetal karyotypes among patients of advanced reproductive age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(51 reference statements)
0
5
0
3
Order By: Relevance
“…61,62 Recent studies based on moderate doses of combined oral contraceptives in human showed a positive effect on trisomic pregnancies, miscarriages, and fecundity. 60,63,64,66,68,69 Therefore, some support for the ovulation hypothesis can be found among epidemiological data, but the overall lack of consensus rendered it important to test itin an experimentally tractable system. Some aspects of the maternal age effect cannot be explained by the ovulation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…61,62 Recent studies based on moderate doses of combined oral contraceptives in human showed a positive effect on trisomic pregnancies, miscarriages, and fecundity. 60,63,64,66,68,69 Therefore, some support for the ovulation hypothesis can be found among epidemiological data, but the overall lack of consensus rendered it important to test itin an experimentally tractable system. Some aspects of the maternal age effect cannot be explained by the ovulation hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…If we accept that, according to this theory, the trisomic oocytes may be retarded in their maturation in comparison with normal oocytes, we have the possibility of reducing trisomic pregnancies with the preservation of the ovarian oocyte reserve by reducing the number of unnecessary ovulations. One method of oocyte reserve preservation is surprisingly obvious: the application of oral contraceptive pills reduces redundant ovulations …”
Section: Discussionmentioning
confidence: 99%
“…The number of disomic oocytes then drops faster than the small proportion of trisomic oocytes . The maternal age effect seems to be an accumulation of T21 oocytes in the ovarian reserve of older women due to the delay of these cells in maturation, which lag behind the normal cells . Hultén et al used fluorescence in situ hybridization (FISH) with two 21 chromosome‐specific probes to determine the copy number of chromosome 21 in ovarian cells from phenotypically normal fetuses at 14‐22 gestational weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Az ovulációgátló hatás következtében persze hosszú távon nem marad több petesejt a petefészekben, hiszen az apoptózis miatt a petesejtek száma folyamatosan csökken. Joggal feltételezhetjük azonban, hogy az apoptózis egyformán hat mind a triszómiás, mind a diszómiás petesejtekre, így az ovuláció gátlásakor a triszómiás/diszómiás petesejtek aránya nem változik [19,20]. Mivel az ovulációk fokozott számával a triszómiás/diszómiás petesejt arány romlik, az ovulációk gátlásával kedvezőbb arányszám "konzerválható".…”
Section: Az Orális Fogamzásgátlók Lehetséges Kedvező Hatása a Triszómiás Sejtek Arányáraunclassified